Development of Interactive Multimedia Based on PJBL Using Lumi on Cell Material as a Science Learning Resource - Putri Salsabila; Tasya Anggyani; Ina Lestari; Niken Arma Hidayah; Muhammad Nasir; Yoichiro Abe (Journal of Natural Science and Integration, 2025)
This study aims to describe the development process and feasibility of Project Based Learning (PJBL) based interactive multimedia developed using Lumi on the topic of cells. The research employed a research and development (R&D) approach, adopting the ADDIE instructional design model, which consists of five stages: analysis, design, development, implementation, and evaluation. The feasibility of the developed multimedia was evaluated by experts in terms of validity and practicality. The results indicated that the PJBL based interactive multimedia developed using Lumi was deemed highly feasible, with an average Aiken’s validity index of 0.85 (very high). The practicality assessment also demonstrated very positive results, with average scores of 93.93 (very practical) from teachers and 91.10 (very practical) from students. The validity evaluation covered four aspects—design, pedagogy, content, and technique—yielding average scores of 0.87, 0.80, 0.85, and 0.86, respectively. These findings suggest that the PJBL based interactive multimedia developed using Lumi is both valid and practical, making it suitable for enhancing the science learning process in junior high schools, particularly in teaching cell conceptsKeywords: cell, development, interactive multimedia, lumi, PJBL